1991
DOI: 10.1007/bf00201492
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated antigen associated with calcium crystals in tobacco anthers

Abstract: We have found and characterized an antigen associated with crystal-containing cells in the stomium and connective tissue of the anthers of Nicotiana tabacum L. (tobacco). The antigen, defined by the monoclonal antibody NtF-8B1, localizes to subcellular regions surrounding the crystals. At the light-microscope level, the antigen is detectable just after the first appearance of crystals in the connective tissue of the anther, and at approximately the same time as the appearance of crystals in the stomium. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A number of histochemical studies have shown that periodic acid-Schiffpositive substances often coat the surfaces of calcium oxalate crystals in plants (see Horner and Wagner, 1995). Immunological studies (Trull et al, 1991) identified an antigen associated with calcium oxalate crystals in anthers of tobacco and other members of the Solanaceae; however, this has not been pursued further. Webb et al (1995) determined that a complex assortment of polypeptides could be solubilized from raphides isolated from grape leaves.…”
Section: How Do Plant Cells Control Crystallization and Crystal Morphmentioning
confidence: 99%
“…A number of histochemical studies have shown that periodic acid-Schiffpositive substances often coat the surfaces of calcium oxalate crystals in plants (see Horner and Wagner, 1995). Immunological studies (Trull et al, 1991) identified an antigen associated with calcium oxalate crystals in anthers of tobacco and other members of the Solanaceae; however, this has not been pursued further. Webb et al (1995) determined that a complex assortment of polypeptides could be solubilized from raphides isolated from grape leaves.…”
Section: How Do Plant Cells Control Crystallization and Crystal Morphmentioning
confidence: 99%
“…c Also referred to as the crystal-containing idioblasts (Trull et al, 1991), intersporangial septum (Bonner and Dickenson, 1989), and hypodermal stomium (Horner and Wagner, 1992). d Collectively referred to as the anther wall.…”
Section: Cell Territories May Play a Role In The Anther Differentiatimentioning
confidence: 99%
“…These include the stomium, the endothecium, and the circular cell cluster (Table 1; Figures 1 and 4). The latter tissue, which is common in solanaceous anthers, is also referred to as the hypodermal stomium (Horner and Wagner, 1992), the intersporangial septum (Keijzer, 1987;Bonner and Dickenson, 1989) and, because it contains calcium oxalate crystals, the crystalcontaining idioblasts (Trull et al, 1991;Horner and Wagner, 1992). The onset of the dehiscence program sets off an ordered series of events within the anther, including (1) the formation of fibrous band thickenings on the endothecial cell walls, (2) degeneration of the circular cell cluster and merging of the two pollen sacs in each theca into a single locule, (3) breakdown of the tapetum and connective, and (4) rupture of the anther at the stomium and pollen release (Figures 1 and 4; Bonner and Dickenson, 1989).…”
Section: Anther Dehiscence Involves the Programmed Destruction Of Spementioning
confidence: 99%
“…1). In contrast, the circular cell cluster consists of highly specialized sub-epidermal cells that accumulate calcium oxalate crystals Wagner 1980, 1992;Trull et al 1991;D'Arcy et al 1996;Iwano et al 2004) and participate in the cell-death process that ultimately unites both locules of each theca into one large pollen chamber ( Fig. 1; Koltunow et al 1990; Goldberg et al 1993Goldberg et al , 1995Beals and Goldberg 1997).…”
mentioning
confidence: 90%